Dampak Motivasi dan Persepsi Biaya Pendidikan terhadap Minat Mahasiswa Akuntansi Mengikuti Pendidikan Profesi Akuntansi (PPAK) dengan Karakteristik Personal Individu Sebagai Variabel Pemoderasi - Listiawati; Merida; Arsadi; Rays, Muh (JOURNAL INTELEKTUAL, 2023)
Introduction/Main: This research discusses the influence of motivation, perceptions of educational costs, and individual personality on students' interest in taking Professional Accounting Education (PPAk). Background Problems: The problem studied in this research is the factors that influence students' interest in taking Accounting Professional Education (PPAk), with a focus on motivation, perceptions of educational costs, and individual personality. Novelty: Lies in combining motivational factors, perceptions of educational costs, and individual personality in the context of students' interest in taking PPAk. Research Methods: This research method is an exploratory study that combines qualitative and quantitative research methods. Finding/Results: Motivation has a significant influence on students' interest in taking PPAk, while perceptions of educational costs do not have a significant influence. Conclusion: Efforts to increase student interest in PPAk should be focused on efforts to grow and maintain motivation. That understanding and maintaining student motivation is very important to increase interest and participation in professional accounting education programs.